Clinical implications of troponin-T elevations following TAVR. (4th February 2022) - Imamura, T; Oshima, A; Onoda, H; Tanaka, S; Ushijima, R; Sobajima, M; Fukuda, N; Ueno, H; Kinugawa, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Baseline and post-procedural elevations in serum troponin-T levels are associated with increased morbidity and mortality following transcatheter aortic valve replacement (TAVR). However, the prognostic impact of change in serum troponin-T level following TAVR remains unknown. Methods: Among the patients with severe aortic stenosis who underwent TAVR, those with baseline serum troponin-T level ≥51.5 ng/L were excluded. The impact of increases in serum troponin-T level to an abnormally high range (≥51.5 ng/L) following TAVR on 2-year cardiovascular death or heart failure readmissions was investigated. Results: Among 189 included patients (median 86 years old, 28% men), serum troponin-T level increased in 79 patients following TAVR. An increase in serum troponin-T was associated with a higher rate of 30-day adverse events, predominantly due to pacemaker implantation for complete atrio-ventricular block, and a higher 2-year cumulative incidence of the primary endpoint (hazard ratio 3.97, 95% confidence interval 1.51-10.4, p = 0.005) adjusted for the use of balloon-expandable valve and post-TAVR pacemaker implantation (Figure 1). Conclusion: Post-procedural increase in serum troponin-T level was associated with adverse clinical outcomes following TAVR.